2005
DOI: 10.1074/jbc.m412994200
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose Deprivation Increases mRNA Stability of Vascular Endothelial Growth Factor through Activation of AMP-activated Protein Kinase in DU145 Prostate Carcinoma

Abstract: The induction of proangiogenic cytokines such as vascular endothelial growth factor (VEGF) is a critical feature of tumor angiogenesis. In the present study, we examined the mechanisms of VEGF gene expression induced by glucose deprivation in cancer cells, a role of AMP-activated protein kinase (AMPK) in the process, and the signal transduction pathway. AMPK functions as an energy sensor to provide metabolic adaptation under ATP-depleting conditions such as hypoxia and nutritional deprivation. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 42 publications
5
102
0
Order By: Relevance
“…We are now focusing on identifying how glucose concentration regulates AM mRNA expression. Our preliminary data suggest that AMPK is implicated in the regulation of AM mRNA expression by glucose concentration (data not shown), in accordance with previous reports, 10,11 and that stability of AM mRNA may not be involved in this regulation, in contrast to a previous report. 12 Tumor cells were implanted s.c. in the back of SCID mice and grown to B5 mm in diameter.…”
Section: Resultssupporting
confidence: 92%
“…We are now focusing on identifying how glucose concentration regulates AM mRNA expression. Our preliminary data suggest that AMPK is implicated in the regulation of AM mRNA expression by glucose concentration (data not shown), in accordance with previous reports, 10,11 and that stability of AM mRNA may not be involved in this regulation, in contrast to a previous report. 12 Tumor cells were implanted s.c. in the back of SCID mice and grown to B5 mm in diameter.…”
Section: Resultssupporting
confidence: 92%
“…In relation to the latter assumption, we have observed that long-term activation of AMPK in rat Sertoli cells increases GLUT1 expression suggesting that this protein is essential for Sertoli cell functioning. The close relationship between AMPK and GLUT1 expression has been previously documented in skeletal muscle cells transfected with a constitutively active mutant form of the catalytic a-subunit of AMPK and in DU145 prostate carcinoma cells stimulated with AICAR (Fryer et al 2002, Yun et al 2005. On the other hand, the decrease in GLUT3 mRNA levels following long-term activation of AMPK can be readily explained by the general inhibitory effect of AMPK activation on anabolic processes (Corton et al 1994).…”
Section: Discussionmentioning
confidence: 90%
“…The first occurred when DU145 PCa cells were subjected to glucose deprivation. Under these conditions, VEGF transcript stability was increased as a result of the stimulation of AMP-activated protein kinase through a mechanism that is still unknown (Yun et al 2005). In addition to this, an isoform of the Wilms' tumor suppressor gene (WT1-A) was found to modestly increase VEGF transcript stability in a hormone-enhanced mechanism when WT1 was stably overexpressed in LNCaP PCa cells.…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 85%